2018
DOI: 10.1080/0284186x.2018.1489144
|View full text |Cite
|
Sign up to set email alerts
|

Frailty status but not age predicts complications in elderly cancer patients: a follow-up study

Abstract: Objectives: The purposes were to investigate the health status of elderly cancer patients by comprehensive geriatric assessment (CGA) and to compare the complications with respect to baseline CGA and to evaluate the need for geriatric interventions in an elderly cancer patients' population. Material: Patients aged !70 years with lung cancer (LC), cancer of the head and neck (HNC), colorectal cancer (CRC), or upper gastro-intestinal cancer (UGIC) are referred to the Department of Oncology for cancer treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Many studies report on frailty as an independent predictor of adverse outcomes [6,[38][39][40]. There is, however, still a paucity of data regarding the effect of incorporating geriatric assessment (thereby assessing frailty) in treatment decision-making on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report on frailty as an independent predictor of adverse outcomes [6,[38][39][40]. There is, however, still a paucity of data regarding the effect of incorporating geriatric assessment (thereby assessing frailty) in treatment decision-making on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…By applying CGA in cancer patients aged 70 years or older, a Danish study group found that up to 87% of patients with cancer types often seen in older patients and often connected to comorbidity were either vulnerable or frail. Patients with lung cancer, colorectal cancer, or gastrointestinal cancer and 14.6% of HNC patients were included in this study ( 23 ). The utility of CGA for older patients with HNC is currently under evaluation in ongoing trials such as GEROP (NCT03053310) or ELAN-ONCOVAL (NCT03614936).…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with esophageal cancer are often malnourished, nutritional intervention should be undertaken (14). Available data also shows that frailty rather than age is a major risk factor of perioperative complications (15). This evidence suggests including patient tailored physical activity in the time between diagnosis and the surgical procedure (16)(17)(18).…”
Section: Preoperative Periodmentioning
confidence: 99%